Advance Care Planning for Intensive Care Patients During the Perioperative Period: A Qualitative Study - Kanako Yamamoto RN, MSN; Yuki Yonekura PhD; Junko Hayama RN, MSN; Taketo Matsubara MD; Hiroyasu Misumi MD, PhD; Kazuhiro Nakayama PhD (SAGE Open Nursing, 2021)
Introduction Patients in intensive care units (ICUs) may transition into an end-of-life phase during treatment. Advance care planning (ACP) for this population has not been studied comprehensively, and support for its implementation is insufficient. Objective This study aims to clarify the ACP support needs among critical perioperative patients. Methods In this qualitative descriptive study, semistructured interviews were conducted with patients previously admitted to the ICU. The survey was conducted from September to November 2019. Participants comprised 13 individuals, who were admitted to the ICU for a period of 3 months to 2 years after surgery. Results The average age of the participants was 63.8 years. The average mechanical ventilation duration following surgery was 24.5 h. The interviews focused on the ACP needs from the preoperative period to discharge. About 90% of the patients thought about the possibility of death before surgery and considered giving advance orders (e.g., “I don't want life-sustaining treatment”). The participants discussed inheritance, work-related matters, and household issues with their families but rarely spoke about treatment and care. Although they examined the content of the advance directives, the medical staff was not informed about them. Patients revealed that they wanted to understand the distinction between life-prolonging and life-saving treatments and discuss it with the medical staff, apart from being educated on ACP. Many patients previously admitted to the ICU are unclear about the difference between life-prolonging and life-saving treatments; this is also true for medical staff. Conclusion Patients who had been admitted to the ICU after high-risk surgery thought they needed help with ACP before surgery. Therefore, patients have the right to know about treatment risks; however, medical staff believes that this is difficult to communicate. Thus, medical staff should consider ways to communicate clearly with patients, including discussing the risks associated with surgery.